The Influence of Competency on The Performance of Functional Officials with Equalization Pathway - Istiyani Nuryati; Sujarwo Sujarwo; Hermanto Hermanto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims to examine competency's influence on functional officials' performance through equalization pathways. Employing an applied causal quantitative approach, the study surveyed functional officials from various universities, with 100 respondents. A questionnaire served as the instrument, encompassing variables such as competency, work motivation, work culture, and the performance of functional officials. Data analysis comprised descriptive and inferential analyses alongside multiple regression analysis techniques aimed at determining variable X's partial and simultaneous influence on variable Y. The findings revealed a positive correlation between competency (X) and performance (Y), indicating that higher competency levels corresponded to higher performance levels. In comparison, lower competency levels were associated with diminished performance. Thus, it can be inferred that a significant relationship exists between competency and the performance of functional officials.